Philosophical Perception of Civil Society - Aghabalyan, Diana (Տիգրան Մեծ)
The article highlights the importance of studying civil society and explores the role of philosophy in shaping it. It discusses different perspectives on the matter, emphasizing how philosophy serves as a theoretical foundation for understanding civil society while also as a field of study playing a pivotal role in its practical implementation.
Keywords: Philosophy